Describing students' mathematical power: Do cognitive styles make any difference? - Fitriyani, Harina; Setyawan, Fariz; Hendroanto, Aan; Istihapsari, Vita (Bulletin of Applied Mathematics and Mathematics Education, 2021)
Mathematical competence refers to the skills of students in reasoning, connection, communication, representation, and problem-solving. Various researchers have massively discussed on how to foster mathematical competence. However, it is just a few of them comprehensively explain from the cognitive styles perspective. This research aims to measure the junior high school students’ mathematical competence based on their cognitive style.This research used a descriptive qualitative approach. There were 35 students took part in the mapping of cognitive styles using the Matching Familiar Figure Test and were then selected representative from the reflective and the impulsive cognitive style to have a further assessment of the mathematical competence using the mathematical competence test. The data analysis used the model of Milles and Huberman. The results showed that there was a difference mathematical competence between the subject having impulsive cognitive style and the one having reflective cognitive style. The percentage of mathematical competence of reflective subject was 69% while the impulsive subject was 56.89%. From all aspects of mathematical competence, the reflective subject tends better ability; for instance, the reflective subject has better ability than the impulsive subject on mathematical connection, mathematical reasoning, mathematical representation, and problem-solving.